PSMA-11-derived dual-labeled PSMA inhibitors for preoperative PET imaging and precise fluorescence-guided surgery of prostate cancer - Eder, Ann-Christin; Roscher, Mareike; Stenau, Esther; Simpfendörfer, Tobias; Teber, Dogu; Maier-Hein, Lena; Haberkorn, Uwe; Eder, Matthias; Kopka, Klaus (Journal of nuclear medicine, 2018)
Resection of tumors using targeted dual-modality probes combining preoperative imaging with intraoperative guidance is of high clinical relevance and might considerably affect the outcome of prostate cancer therapy. This work aimed at the development of dual-labeled prostate-specific membrane antigen (PSMA) inhibitors derived from the established N,N′-bis[2-hydroxy-5-(carboxyethyl)benzyl]ethylenediamine-N,N′-diacetic acid (HBED-CC)-based PET tracer 68Ga-Glu-urea-Lys(Ahx)-HBED-CC (68Ga-PSMA-11) to allow accurate intraoperative detection of PSMA-positive tumors. Methods: A series of novel PSMA-targeting fluorescent dye conjugates of Glu-urea-Lys-HBED-CC was synthesized, and their biologic properties were determined in cell-based assays and confocal microscopy. As a preclinical proof of concept, specific tumor uptake, pharmacokinetics, and feasibility for intraoperative fluorescence guidance were investigated in tumor-bearing mice and healthy pigs. Results: The designed dual-labeled PSMA inhibitors exhibited high binding affinity and PSMA-specific effective internalization. Conjugation of fluorescein isothiocyanate (10.86 ± 0.94 percentage injected dose [%ID]/g), IRDye800CW (13.66 ± 3.73 %ID/g), and DyLight800 (15.62 ± 5.52 %ID/g) resulted in a significantly increased specific tumor uptake, whereas 68Ga-Glu-urea-Lys-HBED-CC-AlexaFluor488 (9.12 ± 5.47 %ID/g) revealed a tumor uptake similar to that of 68Ga-PSMA-11 (4.89 ± 1.34 %ID/g). The first proof-of-concept studies with the clinically relevant candidate 68Ga-Glu-urea-Lys-HBED-CC-IRDye800CW reinforced a fast, specific enrichment in PSMA-positive tumors, with rapid background clearance. With regard to intraoperative navigation, a specific fluorescence signal was detected in PSMA-expressing tissue. Conclusion: This study demonstrated that PSMA-11-derived dual-labeled dye conjugates are feasible for providing PSMA-specific pre-, intra-, and postoperative detection of prostate cancer lesions and have high potential for future clinical translation.